A diaphragm, a method for preparing the diaphragm and a battery

By using a separator containing a porous ceramic layer in a lithium-ion secondary battery, the problem of difficult to ensure self-discharge and safety performance in the prior art while improving the battery magnification and low-temperature performance, achieving a comprehensive improvement of battery performance.

CN119069955BActive Publication Date: 2025-03-04ZHUHAI COSMX BATTERY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411546910.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-04
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

While the existing lithium-ion secondary battery separators improve the magnification, low-temperature discharge and long-cycle performance, it is difficult to ensure the self-discharge and safety performance of the battery.

Method used

Using a separator including a polymer layer and a porous ceramic layer, the porous ceramic layer consisting of inorganic particles, including a first pore having a pore size not less than 0.5 μm and a second pore having a pore size less than 0.5 μm. By adjusting the relationship between the number of the first pores and the Dv50 of the inorganic particles, the porosity and thermal stability of the separator are optimized.

Benefits of technology

It improves the battery's magnification, low-temperature discharge and long-cycle performance, while maintaining the battery's self-discharge and safety performance, reducing the risk of battery failure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119069955B_ABST
    Figure CN119069955B_ABST
Patent Text Reader

Abstract

The present invention provides a diaphragm, a method for preparing the diaphragm, and a battery. The diaphragm includes a polymer layer and a porous ceramic layer located on at least one surface of the polymer layer. The porous ceramic layer includes inorganic particles. The porous ceramic layer includes a first hole with a pore size of not less than 0.5 μm. The porous ceramic layer satisfies: (1) any 10000 μm on the surface of the porous ceramic layer 2 Within the area range of , the number of the first holes is 10 to 1000; (2) 1<D2 / D1<20, D1 is the Dv50 of the inorganic particles, unit: μm, and D2 is the average pore size of the first holes, unit: μm. The separator can ensure that the self-discharge and safety performance of the battery are not affected while improving the battery's rate, low-temperature discharge and long cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to a diaphragm, a method for preparing the diaphragm, and a battery. Background Art

[0002] The diaphragm is a key component of lithium-ion secondary batteries, which directly affects the safety, rate, fast charge cycle and low-temperature discharge performance of lithium-ion secondary batteries. In order to improve the battery rate, low-temperature discharge and fast charge cycle performance of lithium-ion secondary batteries, it is usually necessary to increase the porosity of the diaphragm substrate. However, as the porosity of the diaphragm substrate increases, the puncture strength, thermal shrinkage and other properties of the diaphragm will decrease, thus affecting the self-discharge and safety of the battery.

[0003] Therefore, providing a separator that can improve the battery's rate, low-temperature discharge, and long cycle performance while ensuring that the battery's self-discharge and safety performance are not affected is an urgent problem to be solved. Summary of the invention

[0004] The present invention provides a diaphragm, which can improve the rate, low-temperature discharge and long cycle performance of a battery while ensuring that the self-discharge and safety performance of the battery are not affected.

[0005] The present invention also provides a battery, which includes the above-mentioned diaphragm, so that the battery has excellent low-temperature performance, rate performance, fast charging cycle performance and safety performance.

[0006] In one aspect, the present invention provides a diaphragm, comprising a polymer layer and a porous ceramic layer located on at least one surface of the polymer layer, wherein the porous ceramic layer comprises inorganic particles, the porous ceramic layer comprises a first pore having a pore size of not less than 0.5 μm, and the porous ceramic layer satisfies:

[0007] (1) Any 10000µm on the surface of the porous ceramic layer 2 Within the area range of , the number of the first holes is 10 to 1000;

[0008] (2) 1<D2 / D1<20, D1 is the Dv50 of the inorganic particles, unit: μm, and D2 is the average pore size of the first pores, unit: μm.

[0009] Further, the D1 satisfies: 0.1 μm≤D1≤3 μm; and / or, the D2 satisfies: 0.5 μm≤D2≤10 μm.

[0010] Furthermore, the pore volume of the first pore is V2, unit: cm³ / g; the total pore volume of the porous ceramic layer is V1, unit: cm³ / g, and the V1 and the V2 satisfy: 20%≤V2 / V1×100%≤90%.

[0011] Further, the inorganic particles are selected from one or more of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, and boron nitride;

[0012] And / or, the polymer layer is a porous membrane layer, including at least one of a woven membrane, a non-woven membrane, a polyolefin membrane, and a separator paper, and the material of the polyolefin membrane includes one or more of polyethylene, polypropylene, a composite material of polyethylene and polypropylene, and aramid.

[0013] Furthermore, the thickness of the porous ceramic layer is 1-5 μm;

[0014] And / or, the single-sided surface density of the porous ceramic layer is 1-10 g / m².

[0015] Furthermore, the porous ceramic layer further includes second pores with a pore size less than 0.5 μm.

[0016] In another aspect, the present invention provides a method for preparing the above-mentioned diaphragm, comprising the following steps:

[0017] Adding polymer particles to a first slurry including inorganic particles, a binder and a first solvent, and mixing to obtain a second slurry including the polymer particles;

[0018] Applying the second slurry on at least one surface of the polymer layer to form a ceramic layer after drying, thereby obtaining a diaphragm precursor including the ceramic layer;

[0019] Soaking the ceramic layer in a second solvent, and after the polymer particles are dissolved in the second solvent, performing solid-liquid separation and drying to obtain the diaphragm;

[0020] Wherein, the Dv50 of the polymer particles is D3, and the D3 satisfies the following conditions: 0.5 μm≤D3≤10 μm, 1<D3 / D1<20.

[0021] Further, the weight ratio of the polymer particles to the inorganic particles is 1-20:80-99;

[0022] and / or, the ceramic layer is immersed in the second solvent at 80° C.-100° C. for 2-10 min;

[0023] And / or, the second solvent includes one or more of N-methylpyrrolidone, dimethyl carbonate, ethyl methyl carbonate and dimethylacetamide.

[0024] In yet another aspect, the present invention provides a battery comprising a positive electrode sheet, a negative electrode sheet, and the separator described in the first aspect located between the positive electrode sheet and the negative electrode sheet.

[0025] Furthermore, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on at least one surface of the positive electrode current collector, the positive electrode active layer includes a positive electrode active material, and the positive electrode active material satisfies the following formula 1:

[0026] 0.1<D2 / (10×D4)<1 Formula 1;

[0027] Wherein, D4 is the Dv50 of the positive electrode active material.

[0028] Furthermore, the D4 satisfies: 0.3 μm≤D4≤2 μm, and / or the peeling force between the positive electrode active materials is greater than 1 N / m.

[0029] The diaphragm provided by the present invention can improve the battery's rate, low-temperature discharge and long cycle performance while ensuring that the battery's self-discharge and safety performance are not affected. Specifically, the porous ceramic layer in the diaphragm contains inorganic particles with high stability, which can improve the diaphragm's tolerance to high temperatures and reduce the risk of battery failure. The number of first holes and the relationship between the first holes and the Dv50 of the inorganic particles are further limited. On the one hand, the porosity of the diaphragm can be guaranteed, so that the diaphragm has good lithium ion transmission ability, which helps to improve the battery's rate and low-temperature discharge; on the other hand, the packing density between the inorganic particles can be made appropriate, further improving the thermal stability and liquid storage performance of the diaphragm, thereby helping to further ensure the battery's self-discharge, safety performance and cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A schematic diagram of the structure of a diaphragm provided in one embodiment of the present invention;

[0031] In the figure, 101-polymer layer, 102-porous ceramic layer;

[0032] Figure 2 is a SEM image of the porous ceramic layer included in the diaphragm of Example 1 of the present invention;

[0033] Figure 3 The pore size distribution diagram of the diaphragm provided in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In a first aspect, the present invention provides a diaphragm, Figure 1The separator includes a polymer layer 101 and a porous ceramic layer 102 located on at least one surface of the polymer base layer, the porous ceramic layer 102 includes inorganic particles, the porous ceramic layer includes a first hole with a pore size of not less than 0.5 μm, and the porous ceramic layer meets the following conditions:

[0036] (1) Any 10000µm on the surface of the porous ceramic layer 2 Within the area range of , the number of the first holes is 10 to 1000;

[0037] (2) 1<D2 / D1<20, D1 is the Dv50 of the inorganic particles, unit: μm, and D2 is the average pore size of the first pores, unit: μm.

[0038] In the present invention, by limiting the structure of the porous ceramic layer, the diaphragm can improve the rate, low-temperature discharge and long cycle performance of the battery while ensuring that the self-discharge and safety performance of the battery are not affected. In detail: since the porous ceramic layer contains inorganic particles with good stability, it can improve the diaphragm's tolerance to high temperatures to a certain extent and reduce the risk of battery failure. Further limiting the number of first holes in the porous ceramic layer and the relationship between the first holes and the Dv50 of the inorganic particles can, on the one hand, ensure the porosity of the diaphragm, so that the diaphragm has good lithium ion transmission ability, which helps to improve the rate and low-temperature discharge of the battery; on the other hand, it can increase the packing density between the inorganic particles and improve the thermal stability of the diaphragm, which helps to further ensure the self-discharge, safety performance and cycle life of the battery.

[0039] Exemplarily, D2 / D1 is any value of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, etc.

[0040] Among them, the Dv50 of the material involved in the present invention refers to the particle size value corresponding to 50% (by volume) of the cumulative amount in the material particle size cumulative distribution curve, which can be regarded as the median particle size of the material and is generally obtained by testing with a laser diffraction particle size distribution instrument.

[0041] The number of the first pores is tested using a scanning electron microscope (SEM): Under a scanning electron microscope (SEM), any area of ​​10000µm on the surface of the porous ceramic layer 2 The number of the first holes in the area was recorded; the operation was repeated 5 times to obtain the average value.

[0042] The average pore size D2 of the first pores can also be obtained by SEM testing: Under a scanning electron microscope (SEM), any area of ​​10000µm on the surface of the porous ceramic layer 2In the area, measure the pore size of the pores with a pore size greater than or equal to 0.5µm in the area, record the average pore size of the pores in the area (average pore size = the sum of the pore sizes of all pores / total number of pores), repeat the operation 5 times and take the average value as D2.

[0043] In a specific embodiment, the D1 satisfies: 0.1 μm≤D1≤3 μm; and / or, the D2 satisfies: 0.5 μm≤D2≤10 μm.

[0044] Exemplarily, D1 is any value among 0.5μm, 0.7μm, 0.8μm, 1.0μm, 1.2μm, 1.5μm, 1.7μm, 1.8μm, 2.0μm, 2.2μm, 2.5μm, 2.7μm, 2.8μm, etc., and D2 is any value among 1.0μm, 1.5μm, 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 5.0μm, 5.5μm, 6.0μm, 6.5μm, 7.0μm, 7.5μm, 8.0μm, 8.5μm, 9.0μm, 9.5μm, etc.

[0045] In order to further increase the packing density between inorganic particles, make the diaphragm have good heat resistance, thereby ensuring the safety performance of the battery, and / or, further increase the porosity of the diaphragm, make the diaphragm have good ion conductivity, thereby ensuring the low temperature and rate performance of the battery, in a specific embodiment, the pore volume of the first pore is V2, unit: cm³ / g; the total pore volume of the porous ceramic layer is V1, unit: cm³ / g, V1 and V2 satisfy: 20%≤V2 / V1×100%≤90%.

[0046] In some embodiments, the above-mentioned V2 / V1 can be tested using a mercury porosimeter test method, first testing the pore size distribution of the entire diaphragm, then testing the pore size distribution of the polymer layer, subtracting the pore size distribution of the polymer layer from the overall pore size distribution to obtain the pore size distribution of the ceramic layer, and then dividing the integral area of ​​pores greater than or equal to 0.5 um by the total integral area to obtain V2 / V1.

[0047] In some embodiments, 50≤V2 / V1×100%≤80%; more specifically, V2 / V1×100% is any value of 21%, 23%, 25%, 27%, 30%, 35%, 37%, 40%, 45%, 47%, 50%, 55%, 57%, 60%, 65%, 67%, 70%, 75%, 77%, 80%, etc.

[0048] In a specific embodiment, the inorganic particles are selected from one or more of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, and boron nitride.

[0049] In another specific embodiment, the diaphragm used in the present invention is a composite diaphragm, including a polymer layer 101 and a porous ceramic layer 102 located on at least one surface of the polymer layer 101, the polymer layer 101 is a porous membrane layer, including at least one of a woven membrane, a non-woven membrane, a polyolefin membrane, and a diaphragm paper, and the material of the polyolefin membrane includes one or more of polyethylene, polypropylene, a composite material of polyethylene and polypropylene, and aramid.

[0050] Exemplarily, the porous ceramic layer further includes auxiliary materials, and the auxiliary materials include at least one of a dispersant, a binder and a thickener.

[0051] The dispersant is selected from one or more of fluoroalkyl methoxy alcohol ether, polyoxyethylene alkylamine, sodium butylnaphthalene sulfonate, sodium arylnaphthalene sulfonate, sodium dodecylbenzene sulfonate, sodium alkyl sulfate, sodium polyacrylate, sodium polymetaphosphate, sodium silicate, and sodium dodecyl sulfate.

[0052] The binder is selected from one or more of styrene-butadiene rubber, polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene, polyvinylidene fluoride-tetrafluoroethylene, polyvinylidene fluoride-hexafluoroethylene, polyvinylidene fluoride-hexafluoropropylene, styrene acrylic emulsion, polyethyl acrylate, polymethyl methacrylate, polybutyl methacrylate, polyvinyl alcohol, ethylene-vinyl acetate copolymer, polyvinyl acetate, and polyurethane.

[0053] The thickener is selected from one or both of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.

[0054] In a specific embodiment, the thickness of the porous ceramic layer is 1-5 μm. The thickness of the porous ceramic layer refers to the thickness of the porous ceramic layer on one surface of the polymer base layer. This embodiment adjusts the thickness of the ceramic layer to ensure that the diaphragm has good heat resistance, thereby making the battery have good safety performance; on the other hand, it ensures that the diaphragm is not too thick to affect the volume energy density of the battery.

[0055] In a specific embodiment, the single-sided surface density of the porous ceramic layer is 1-10 g / m². The single-sided surface density of the porous ceramic layer refers to the surface density of the porous ceramic layer on one surface of the polymer base layer. This embodiment adjusts the surface density of the ceramic layer to ensure that the diaphragm has good insulation properties, thereby making the battery have good safety performance; on the other hand, it ensures that the diaphragm is not too heavy to affect the weight energy density of the battery.

[0056] Exemplarily, the single-sided surface density of the porous ceramic layer can be tested by a method comprising the following process: peeling off a porous ceramic layer sample within a unit area from the diaphragm, weighing the total mass of the sample using a high-precision balance, and dividing the total mass of the sample by the area to obtain the single-sided surface density of the porous ceramic layer.

[0057] In a specific embodiment, the porous ceramic layer further comprises second pores with a pore size less than 0.5 μm, wherein the second pores are micropores formed by the accumulation of ceramic particles themselves.

[0058] In a second aspect, the present invention provides a method for preparing the above-mentioned diaphragm, comprising the following steps:

[0059] Adding polymer particles to a first slurry including inorganic particles, a binder and a first solvent, and mixing to obtain a second slurry including the polymer particles;

[0060] Applying the second slurry on at least one surface of the polymer layer to form a ceramic layer after drying, thereby obtaining a diaphragm precursor including the ceramic layer;

[0061] Soaking the ceramic layer in a second solvent, and after the polymer particles are dissolved in the second solvent, performing solid-liquid separation and drying to obtain the diaphragm;

[0062] Wherein, the Dv50 of the polymer particles is D3, and the D3 satisfies the following conditions: 0.5 μm≤D3≤10 μm, 1<D3 / D1<20.

[0063] In the above preparation method, a second slurry including soluble polymer particles is first coated on the surface of the polymer layer, and the polymer particles form placeholders on the surface of the polymer layer. Then, a second solvent is used to dissolve the polymer particles, and the space occupied by the polymer particles is vacated. After drying, stable first pores are formed, and second pores with smaller pore sizes are formed between the inorganic particles.

[0064] It can be understood that the main difference between the above membrane precursor and the final membrane is that the first pore is not contained; the above first solvent is a solvent that does not dissolve the polymer particles, and the second solvent is a solvent that can dissolve the polymer particles. For example, the polymer particles are selected from polymers polymerized from at least one monomer of acrylic acid, acrylic acid ester, styrene, and acrylonitrile, such as polymer particles are polyacrylate, polymethyl methacrylate, polymethyl methacrylate-acrylonitrile copolymer, etc. The first solvent is water, and the second solvent includes one or more of N-methylpyrrolidone (NMP), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and dimethylacetamide (DMAC).

[0065] In a specific embodiment, the method further includes accelerating the dissolution rate of the polymer particles by heat treatment. More specifically, the polymer particles are immersed in the second solvent at 80°C-100°C for 2-10 minutes to change the polymer particles from granular to non-granular and completely dissolve in the second solvent. The membrane precursor is extracted by water washing and dried at a temperature of 40-80°C to obtain the membrane.

[0066] The mass ratio of the components of the above-mentioned first slurry is not particularly limited in the present invention, and the technicians can continue to adjust it according to the required thickness and strength of the porous ceramic layer. In a specific embodiment, in the first slurry, the ratio of the inorganic particles, polymer particles, binder, dispersant, thickener and first solvent is 27.6:3:1.2:0.6:0.6:67, calculated by weight.

[0067] Exemplarily, the binder is selected from one or more of styrene-butadiene rubber, polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene, polyvinylidene fluoride-tetrafluoroethylene, polyvinylidene fluoride-hexafluoroethylene, polyvinylidene fluoride-hexafluoropropylene, styrene acrylic emulsion, polyethyl acrylate, polymethyl methacrylate, polybutyl methacrylate, polyvinyl alcohol, ethylene-vinyl acetate copolymer, polyvinyl acetate, and polyurethane;

[0068] Said No. A slurry may also include a dispersant and a thickener;

[0069] The dispersant is selected from one or more of fluoroalkyl methoxy alcohol ether, polyoxyethylene alkylamine, sodium butylnaphthalene sulfonate, sodium arylnaphthalene sulfonate, sodium dodecylbenzene sulfonate, sodium alkyl sulfate, sodium polyacrylate, sodium polymetaphosphate, sodium silicate, and sodium dodecyl sulfate.

[0070] The thickener is selected from one or both of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.

[0071] In order to further improve the porosity of the porous ceramic layer, in one specific embodiment, the weight ratio of the polymer particles to the inorganic particles is 1-20:80-99.

[0072] In a third aspect, the present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet, and the separator described in the first aspect located between the positive electrode sheet and the negative electrode sheet.

[0073] In a specific embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on at least one surface of the positive electrode current collector, the positive electrode active layer includes a positive electrode active material, and the positive electrode active material satisfies the following formula 1:

[0074] 0.1<D2 / (10×D4)<1 Formula 1;

[0075] Wherein, D4 is the Dv50 of the positive electrode active material.

[0076] In the above embodiment, by adjusting the relationship between the Dv50 of the positive electrode active material and the pore size of the first pore, the positive electrode active material can have a larger specific surface area, so that the positive electrode sheet has more charging and discharging channels; in addition, the pore size of the first pore and the Dv50 of the positive electrode active material satisfy the relationship shown in the above formula 1, and the Li+ ion conductivity of the diaphragm can be further improved, and the transmission efficiency of Li ions can be improved. If D2 / (10×D4) is greater than 1, the particle size of the positive electrode active material is small, which may block the pores of the diaphragm, resulting in obstruction of Li ion transmission, thereby affecting the electrochemical performance of the battery. On the contrary, if D2 / (10×D4) is less than 0.1, the particle size of the positive electrode active material is large, which may reduce the diffusion path of Li ions, thereby reducing the power performance of the battery.

[0077] In order to ensure that the pores of the diaphragm are not blocked by the positive electrode active material and at the same time ensure that the transmission rate of Li ions is within a higher range, in a specific embodiment, the D4 satisfies: 0.3 μm≤D4≤2 μm.

[0078] The low bonding strength between the positive electrode active materials (smaller peeling force) will cause gaps and cracks to form inside the electrode sheet, increase the internal resistance of the battery, reduce the contact area of ​​the effective active material, and be detrimental to the thermal cycle of the battery. Therefore, in order to further ensure the thermal cycle stability of the battery, in a specific embodiment, the peeling force between the positive electrode active materials is greater than 1N / m.

[0079] It can be understood that the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on at least one surface of the positive electrode current collector, and the positive electrode active layer includes the positive electrode active material.

[0080] Exemplarily, the positive electrode active layer specifically includes the positive electrode active material, the conductive agent and the binder, and the positive electrode active material can be selected from one or more of lithium nickelate, lithium titanate, lithium cobaltate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum, lithium iron phosphate, and lithium manganate. The positive electrode current collector can be a conventional positive electrode current collector in the art, such as aluminum foil, etc. The mass fraction of the positive electrode active material in the positive electrode active layer is 94%-99%, the mass fraction of the binder is 0.5%-5%, and the mass fraction of the conductive agent is 0.5%-3%; the positive electrode binder is selected from one or more of polyvinylidene fluoride, polyimide, polyacrylic acid, polytetrafluoroethylene, perfluorosulfonic acid ionomer, polyacrylonitrile, acrylic acid-modified PVDF, polyacrylate polymers, polyimide, styrene-butadiene rubber, and styrene-acrylic rubber.

[0081] Exemplarily, the peeling force between the positive electrode active materials can be obtained by a method comprising the following steps:

[0082] The pressure-sensitive tape is bonded to the stainless steel plate, and then one side of the positive active layer of the positive electrode sheet is bonded to the pressure-sensitive tape. The tensile testing machine clamps the negative electrode sheet for 180° peeling. The required peeling force is recorded as FN / m. If F is greater than or equal to 1 N / m, continue to observe the thickness of the positive active layer remaining on the current collector, otherwise it is determined that the peeling force between the positive active materials is less than or equal to 1N / m. If the thickness of the residual positive active layer is greater than 1μm, it means that the peeling force between the positive active materials in the positive active layer is greater than the peeling force between the positive active layer and the current collector, which means that the peeling force between the positive active materials is greater than 1 N / m.

[0083] Exemplarily, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on at least one surface of the negative electrode current collector, the negative electrode active layer includes a negative electrode active material, a conductive agent, a binder and a thickener, the negative electrode active material can be a negative electrode active material for a battery known in the art, such as one or more of a carbon-based material, a silicon-based material, a tin-based material, and a titanium-based material; specifically, it can be one or more of artificial graphite, natural graphite, soft carbon, hard carbon, elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, silicon alloys, elemental tin, tin oxide compounds, tin alloys, elemental titanium, titanium oxide compounds, and titanium alloys. The negative electrode current collector can be a conventional negative electrode current collector in the art, such as copper foil, etc. The mass fraction of the negative electrode active material in the negative electrode active layer is 92%-98%, the mass fraction of the binder is 0.5%-3%, the mass fraction of the conductive agent is 0.5%-2.5%, and the mass fraction of the thickener is 0.5%-2.5%.

[0084] The conductive agent and binder used in the positive electrode active layer and the negative electrode active layer may be the same or different. The conductive agent includes one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene. The binder includes one or more of polyvinylidene fluoride (PVDF), a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, polyhexafluoropropylene, and styrene-butadiene rubber (SBR). The thickener includes carboxymethyl cellulose sodium (CMC-Na) and the like.

[0085] The battery of the present invention can be manufactured according to conventional methods in the art, such as stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, assembling the battery cell through a winding process or a stacking process, and then packaging and baking, injecting the electrolyte, and then hot pressing and other processes to obtain the battery.

[0086] Exemplarily, the battery further includes an electrolyte, and the present invention does not specifically limit the above-mentioned electrolyte, for example, an electrolyte including an organic solvent and an electrolyte salt is selected. Among them, the organic solvent is used as a medium for transmitting ions in the electrochemical reaction, and an organic solvent for battery electrolyte known in the art can be used, for example: including ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate ...ethyl propionate (EMC), dipropyl carbonate (DPC), methyl propionate (MP), ethyl propionate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EPC), ethyl propionate (EMC), dipropyl carbonate (DPC), methyl propionate (MP), ethyl propionate (EPC), butylene carbonate (BC), butylene carbonate (BC), fluoroethylene carbonate At least one of ester (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE); the electrolyte salt is used as a source of ions, and the electrolyte salt for battery electrolyte known in the art can be used, for example: at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorobisoxalatephosphate, lithium tetrafluorooxalatephosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium perfluorobutylsulfonate, and lithium fluorinated fatty acid.

[0087] In a specific embodiment, the organic solvent of the electrolyte consists of: EMC (10-70 parts), EA (10-70 parts), EC (15-40 parts), and also includes bisfluorosulfonyl imide lithium salt and lithium hexafluorophosphate, the content of the bisfluorosulfonyl imide lithium salt is 2~20 parts, preferably 3~9 parts; the concentration of lithium hexafluorophosphate is 0.3~1.8mol / L; preferably 0.8~1.5mol / L.

[0088] The present invention is described in detail by taking lithium-ion batteries as an example:

[0089] Example 1

[0090] This example provides a diaphragm, the diaphragm includes a polymer layer and a porous ceramic layer located on one surface of the polymer base layer, the porous ceramic layer includes 20 parts of inorganic particles: aluminum oxide, 2 parts of a binder: polyvinylidene fluoride, 4 parts of a thickener: fluoroalkyl methoxy alcohol ether, and 2 parts of a dispersant: sodium carboxymethyl cellulose, the porous ceramic layer includes a first hole with a pore size of 0.5 μm and a second hole with a pore size less than 0.5 μm, and the porous ceramic layer meets the following conditions: any 10000 μm on the surface of the porous ceramic layer 2Within the area range, the number of the first pores is 165, the Dv50 of the inorganic particles is 0.8μm, and the pore volume of the first pores accounts for 30% of the total pore volume of the porous ceramic layer; the thickness of the porous ceramic layer is 2μm; the polymer layer is a polyethylene layer with a thickness of 7μm and a porosity of 38%; the single-sided surface density of the porous ceramic layer is 2.6g / m².

[0091] The preparation method thereof comprises the following steps:

[0092] 1) 20 parts of aluminum oxide, 4 parts of sodium carboxymethyl cellulose, 2 parts of polyvinylidene fluoride, 2 parts of fluoroalkyl methoxy alcohol ether, and 72 parts of deionized water are mixed and stirred to obtain a first slurry;

[0093] 2) Take 100 parts of the first slurry, add polymer particles (polymethyl methacrylate-acrylonitrile copolymer particles), mix and stir to obtain a second slurry; wherein the Dv50 of the polymethyl methacrylate-acrylonitrile copolymer particles is 5µm, and the weight ratio of the methyl methacrylate-acrylonitrile copolymer particles to the alumina is shown in Table 1.

[0094] 3) coating the second slurry on the upper and lower surfaces of the polymer base layer by micro-gravure printing, and obtaining a membrane precursor after drying;

[0095] 4) The membrane precursor is immersed in NMP at 80° C. for 2 min, and then washed with water and dried to obtain the membrane.

[0096] Example 2-12

[0097] A diaphragm is provided respectively, which is different from Example 1 in that the parameters in Table 1 are changed.

[0098] Comparative Examples 1-4

[0099] A diaphragm is provided respectively, which is different from Example 1 in that the parameters in Table 1 are changed.

[0100] Comparative Example 5

[0101] This example provides a diaphragm, which includes a polymer layer and a porous ceramic layer located on one surface of the polymer base layer. The porous ceramic layer includes 20 parts of inorganic particles: aluminum oxide, 2 parts of a binder: polyvinylidene fluoride, 4 parts of a thickener: fluoroalkyl methoxy alcohol ether, and 2 parts of a dispersant: sodium carboxymethyl cellulose, by mass. The porous ceramic layer only includes a second pore with a pore size less than 0.5μm, and the thickness of the porous ceramic layer is 2μm; the polymer layer is a polyethylene layer with a thickness of 7μm and a porosity of 50%; the single-sided surface density of the porous ceramic layer is 3.4g / m².

[0102] The preparation method thereof comprises the following steps:

[0103] 1) 20 parts of aluminum oxide, 4 parts of sodium carboxymethyl cellulose, 2 parts of polyvinylidene fluoride, 2 parts of fluoroalkyl methoxy alcohol ether, and 72 parts of deionized water are mixed and stirred to obtain a first slurry;

[0104] 2) The first slurry is coated on the upper and lower surfaces of the polymer base layer by micro-gravure, and a diaphragm is obtained after drying.

[0105] Table 1:

[0106]

[0107] Test Example 1

[0108] This example provides a series of batteries, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, and the preparation thereof includes the following steps:

[0109] (1) Preparation of positive electrode

[0110] The positive electrode active material (lithium iron phosphate (LFP) doped with titanium and vanadium, Dv50 = 1µm), the positive electrode binder (polyvinylidene fluoride (PVDF)), and the positive electrode conductive agent (acetylene black) are mixed in a weight ratio of 96.5:1.5:2.0, and N-methylpyrrolidone (NMP) is added, and stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode slurry with uniform fluidity; the positive electrode slurry is evenly coated on the surface of both sides of an aluminum foil with a thickness of 10μm; the coated aluminum foil is baked in an oven with 5 different temperature gradients (95℃±5℃, 100℃±5℃, 103℃±5℃, 100℃±5℃, 95℃±5℃), and then dried in an oven at 120℃ for 8h, and then rolled and cut to obtain the required positive electrode sheet.

[0111] (2) Preparation of negative electrode

[0112] The negative electrode active material (artificial graphite), the negative electrode conductive agent (including 0.2 parts by weight of single-walled carbon nanotubes (SWCNT) and 1 part by weight of conductive carbon black (SP)), and the negative electrode binder (including 1 part by weight of sodium carboxymethyl cellulose (CMC-Na) and 2.5 parts by weight of styrene-butadiene rubber (SBR)) are mixed in a weight ratio of 95.3:1.2:3.5, and a slurry is prepared by a wet process (water is added to the mixture formed by the above mixing, and the mixture is stirred under the action of a vacuum stirrer until the mixture becomes a negative electrode slurry with uniform fluidity), and the slurry is coated on the surfaces of both sides of the negative electrode collector (copper foil), and the negative electrode sheet is obtained by drying (temperature: 85°C, time: 5h), rolling and die-cutting.

[0113] (3) Preparation of electrolyte

[0114] In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), 36 parts by weight of ethyl methyl carbonate (EMC), 27 parts by weight of ethyl acetate (EA), and 13.5 parts by weight of ethylene carbonate (EC) were mixed to obtain a mixed solution 1, 4.5 parts by weight of VC were added to the mixed solution 1 to obtain a mixed solution 2, 6.5 parts by weight of LiFSi and 12.5 parts by weight of lithium hexafluorophosphate were slowly added to the mixed solution 2, and the mixture was stirred to obtain a non-aqueous electrolyte.

[0115] (4) Preparation of lithium-ion batteries

[0116] The positive electrode sheet of step (1), the separator of each embodiment and comparative example, and the negative electrode sheet of step (2) are respectively wound to obtain a bare cell without liquid injection; the bare cell is placed in an outer packaging foil, and the electrolyte of step (3) is injected into the dried bare cell. After vacuum packaging, standing, formation, shaping, sorting and other processes, the desired lithium-ion battery is obtained.

[0117] Test Example 2-4

[0118] The same test example 1 as the test example 1 was used for the diaphragm test, except that the positive electrode active material Dv50 of the positive electrode sheet was changed as shown in Table 2.

[0119] Test Case

[0120] The above batteries were tested for the following properties:

[0121] (1) -20℃ cycle test

[0122] Place the lithium-ion battery in a (-20±2)℃ environment and let it stand for 2-3 hours. When the battery reaches (25±2)℃, charge the battery at 1C constant current with a cutoff current of 0.05C. After the battery is fully charged, let it sit for 5 minutes and then discharge it at 1C constant current to a cutoff voltage of 3.0V. Record the highest discharge capacity of the first three cycles as the initial capacity Q. When the cycle reaches 10 times, record the last discharge capacity Q1 of the battery. The capacity retention rate (%) = Q1 / Q×100%. Record the results in Table 2.

[0123] (2) 25℃ cycle test

[0124] Place the lithium-ion battery in a (25±2)℃ environment and let it stand for 2-3 hours. When the battery reaches (25±2)℃, charge the battery at 3C constant current with a cutoff current of 0.05C. After the battery is fully charged, let it sit for 5 minutes and then discharge it at 3C constant current to a cutoff voltage of 3.0V. Record the highest discharge capacity of the first three cycles as the initial capacity Q. When the cycle reaches 1000 times, record the last discharge capacity Q1 of the battery. The capacity retention rate (%) = Q1 / Q×100%. Record the results in Table 2.

[0125] (3) 130℃ thermal shock test

[0126] The lithium-ion battery was heated in a convection air box at a starting temperature of (25±3)°C, a temperature change rate of (5±2)°C / min, and the temperature was raised to (130±2)°C. The test was terminated after maintaining for 60 minutes, and the battery status was recorded. The results are recorded in Table 2.

[0127] Rate performance test

[0128] Place the lithium-ion battery in a (25±2)℃ environment and let it stand for 2-3 hours. When the battery body reaches (25±2)℃, the battery is charged at 0.5C constant current with a cutoff current of 0.05C. After the battery is fully charged, let it sit for 5 minutes to obtain the battery capacity Q. Then, it is discharged at 1C constant current to a cutoff voltage of 3.0V. Then, the battery is charged at 5C constant current with a cutoff current of 0.05C to obtain the capacity Q1. The charging capacity retention rate (%) = Q1 / Q×100%. The results are recorded in Table 2.

[0129] Self-discharge test:

[0130] Place the lithium-ion battery in a (25±2)℃ environment and let it stand for 2-3 hours. When the battery body reaches (25±2)℃, charge the battery at 0.5C constant current with a cut-off current of 0.05C. Place the fully charged battery in a (25±2)℃ environment for 48H and test the voltage V. After 72H, test the voltage V1. The self-discharge K value = (V-V1) / 72. Record the results in Table 2.

[0131] Table 2:

[0132]

[0133] It can be seen from Table 2 that, compared with the comparative example, the diaphragm provided in the embodiment improves the rate, low-temperature discharge and long cycle performance of the battery while ensuring that the self-discharge and safety performance of the battery are not affected.

[0134] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A battery comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, characterized in that: The separator includes a polymer layer and a porous ceramic layer located on at least one surface of the polymer layer, the porous ceramic layer includes inorganic particles, the porous ceramic layer includes first pores with a pore size of not less than 0.5 μm, and the porous ceramic layer satisfies: (1) Any 10000µm on the surface of the porous ceramic layer 2 Within the area range of , the number of the first holes is 10 to 1000; (2) 1<D2 / D1<20, D1 is the Dv50 of the inorganic particles, unit: μm, and D2 is the average pore size of the first pores, unit: μm; The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on at least one surface of the positive electrode current collector, wherein the positive electrode active layer includes a positive electrode active material, and the positive electrode active material satisfies the following formula 1: 0.1<D2 / (10×D4)<1 Formula 1; Wherein, D4 is the Dv50 of the positive electrode active material.

2. The battery according to claim 1, characterized in that The D1 satisfies: 0.1 μm ≤ D1 ≤ 3 μm; and / or, the D2 satisfies: 0.5 μm ≤ D2 ≤ 10 μm.

3. The battery according to claim 1, characterized in that The pore volume of the first pore is V2, unit: cm³ / g; the total pore volume of the porous ceramic layer is V1, unit: cm³ / g, and V1 and V2 satisfy: 20%≤V2 / V1×100%≤90%.

4. The battery according to claim 1, characterized in that The inorganic particles are selected from one or more of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, and boron nitride; And / or, the polymer layer is a porous membrane layer, including at least one of a woven membrane, a non-woven membrane, a polyolefin membrane, and a separator paper, and the material of the polyolefin membrane includes one or more of polyethylene, polypropylene, a composite material of polyethylene and polypropylene, and aramid.

5. The battery according to claim 1, characterized in that The thickness of the porous ceramic layer is 1-5 μm; And / or, the single-sided surface density of the porous ceramic layer is 1-10 g / m².

6. The battery according to any one of claims 1 to 5, characterized in that: The porous ceramic layer further includes second pores with a pore size less than 0.5 μm.

7. The battery according to claim 1, characterized in that The D4 satisfies: 0.3 μm≤D4≤2 μm, and / or the peeling force between the positive electrode active materials is greater than 1 N / m.

8. A method for preparing a battery according to any one of claims 1 to 7, characterized in that: The following steps are involved: Adding polymer particles to a first slurry including inorganic particles, a binder and a first solvent, and mixing to obtain a second slurry including the polymer particles; Applying the second slurry on at least one surface of the polymer layer to form a ceramic layer after drying, thereby obtaining a diaphragm precursor including the ceramic layer; Soaking the ceramic layer in a second solvent, and after the polymer particles are dissolved in the second solvent, performing solid-liquid separation and drying to obtain the diaphragm; Wherein, the Dv50 of the polymer particles is D3, and the D3 satisfies the following conditions: 0.5 μm≤D3≤10 μm, 1<D3 / D1<20.

9. The preparation method according to claim 8, characterized in that: The weight ratio of the polymer particles to the inorganic particles is 1-20:80-99; and / or, the ceramic layer is immersed in the second solvent at 80° C.-100° C. for 2-10 min; And / or, the second solvent includes one or more of N-methylpyrrolidone, dimethyl carbonate, ethyl methyl carbonate and dimethylacetamide.

Citation Information

Patent Citations

  • Membrane for an electrochemical device, electrochemical device comprising the membrane, and method of manufacturing an

    CN114868301A

  • Lithium manganese iron phosphate battery

    CN116914087A